Needs for Counselling in Communication of Family Planning Program in Decentralizatim Era in Purbalingga - Dyah Retna Puspita; Eri Wahyuningsih; Dwi Hapsari (Jurnal Komunikasi Pembangunan, 2014)
AbstractThis study examined the husbands’ perspective about family  planning counseling in Purbalingga District. Target of this study were 30 husbands who experienced gender role shifting. Data obtained through interview and focus group discussions. Results of this  research were: first, they initially had experience of gender role conflict; second, they never involved in family planning counseling whereas they need information about family harmony, reproductive health, child development and other related issues.Keywords: family planning counseling, gender role shift, gender role conflict